ChemInform Abstract: Synthesis of Vinyl Trifluoromethyl Thioethers via Copper‐Mediated Trifluoromethylthiolation of Vinyl Bromides. Issue 30 (July 2015) - Huang, Yangjie; Ding, Jianping; Wu, Chuyi; Zheng, Huidong; Weng, Zhiqiang
Abstract The reaction of various vinyl bromide substrates with copper complex (II) affords the desired thioethers with good to excellent yields.